Self-Efficacy and Coping Mechanism in Patients with Chronic Kidney Disease undergoing Hemodialysis: A Correlational Study - Merentek, Natalia Nadia; Fitriani, Fitriani; Fernandez, Gratsia Victoria (Omni Nursing Journal, 2026)
Background: Chronic kidney disease (CKD) is a global health problem with increasing disease prevalence and poor prognosis.North Sulawesi is the third province with the highest number of chronic kidney disease sufferers in Indonesia. Objective: This study aimed to determine the relationship between self-efficacy and coping mechanisms in chronic kidney disease patients undergoing hemodialysis. Methods: This study used a quantitative research method with a cross-sectional study approach. The sampling technique used in this study was purposive sampling. Data collected used sociodemographic questionnaire, the Chronic Kidney Disease Self Efficacy (CKD-SE) questionnaire, and the Ways of Coping questionnaire. The Gamma statistical test was employed to determine the relationship between self-efficacy and coping mechanism. Results: The number of respondents in this study was 140 respondents. The results of the Gamma correlation test showed a relationship between self-efficacy and coping mechanisms, with a significance value of 0.000 and a coefficient value of 0.415. This indicated a positive and statistically significant relationship between self-efficacy and coping mechanisms. Conclusion: There is a significant relationship between self-efficacy and coping mechanisms in chronic kidney disease patients undergoing haemodialysis. The higher the respondent's self-efficacy, the more adaptive the coping mechanism. It is suggested that healthcare providers implement targeted interventions to enhance patients’ self-efficacy, as strengthening self-efficacy may promote more adaptive coping mechanisms among individuals undergoing haemodialysis.